Penerapan Model Pembelajaran Kooperatif Tipe TGT (Teams Games Tournament) untuk Meningkatkan Keaktifan Belajar PKN Peserta Didik Kelas II-B SDN 1 Bengkel - Dzulkhairani, Intan; Izur Mizwar; Ilham (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2024)
This research was conducted on class II-B students at SDN 1 Bengkel in PKN learning process. The Aims of this reasearch is to increase the students activity by using cooperative learning type Teams Games Tournament (TGT). This research used Â Classroom Action Research (PTK) with two cycles, data on student activity was collected and analyzed qualitatively. The results show a significant increase in students' learning activeness from pre-cycle activities to cycle II. The average percentage of active learning increased from 36% in the pre-cycle, to 45% in cycle I and reached 89% in cycle II. This confirms that the implementation of the Teams Games Tournament (TGT) type cooperative learning model is effective in increasing the activeness of PKN learning for class II_B students at SD Negeri 1 Bengkel.